Tests for clinical assessment of the stand-to-sit/ sit-to-stand in subjects post-stroke: a systematic review. - Silva, Paula Fernanda de Sousa; Gusmão, Amanda Ferreira; Franco, Juliane; Quintino, Ludmylla Ferreira; Faria, Christina Danielli Coelho de Morais (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Individuals with stroke usually show limitations in the performance of daily activities. Among the most limited activities is the stand-up/sit-down, which limitation in performance is a major cause of disability in this population. Objective: The aim of the present study was to describe the clinical tests used to evaluate the stand-up/sit-down in individuals with stroke, considering their protocols and properties. Method: A systematic literature review following the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) protocol was performed. Systematic literature searches on the following databases MEDLINE/SCIELO/LILACS/PEDro was performed, using search strategies that included terms referring to tests and individuals with stroke. The inclusion criteria were: use of a clinical test to evaluate the stand-up/sit-down in individuals with stroke and be published in any language until april/2013. Results: Fifteen studies were included, which used the test of three repetitions (n=1/15), number of repetitions in 30s (n=1/15) and 60s (n=1/15), and the five repetitions test (n=12/15), for which was investigated reliability with intraclass correlation coefficients (ICC) (n=2/12, 0.89≤ICC≤0.99), sensibility/specificity (n=2/12, 67%-83%/72-75%) and validity with pearson correlation coefficients (r) (n=1/12, 0.75≤r≤0.83). Most part of the studies (n=8/15) used chair with seat height fixed and reported the number of repetitions of the test (n=7/15), performed with one (n=3/8), two (n=2/8) or three repetitions (n=3/8). Conclusion: The test of five repetitions was used more often in individuals with stroke and the only one for which measurement properties was investigated, which results were adequate. However, standardization of this test considering determining factors for the evaluation of stand-up/sitdown, as chair height and number of repetitions, are still needed.